Identifying the roles of miR-17 in ciliogenesis and cell cycle - Alanazi, Ashwaq; Barui, Ayan K.; Mohieldin, Ashraf M.; Gupta, Ankan; Ramchandran, Ramani; Nauli, Surya M. (Frontiers in Cell and Developmental Biology, 2024)
Emerging evidence suggests a significant contribution of primary cilia to cell division and proliferation. MicroRNAs, especially miR-17, contribute to cell cycle regulation and proliferation. Recent investigations have highlighted the dysregulated expression of miR-17 in various malignancies, underlining its potential role in cancer. However, the correlation between primary cilia and miR-17 has yet to be fully elucidated. The present study examines the presence of miR-17 in primary cilia. The miR-17 expression is studied in selected ciliary protein knockdown cells. Using in situ hybridization (ISH), we identified the subcellular localization of miR-17 in both cilium and cell body. We confirmed the importance of miR-17, progesterone receptor membrane component-2 (PGRMC2), and monosialodihexosylganglioside (GM3S) in cilia formation, as shown by the significant reduction in cilia and cilia length in knockdown cells compared to control. We also demonstrated the involvement of PGRMC2, GM3S, polycystin-2 (PKD2), and miR-17 in cellular proliferation and cell growth. Our studies revealed a hyperproliferative effect in the knockdown cells compared to control cells, suggesting the regulatory roles of PGRMC2/GM3S/PKD2/miR-17 in promoting cell proliferation. Overall, our studies conclude that ciliary proteins are involved in cell division and proliferation. We further hypothesize that primary cilia can serve as compartments to store and control genetic materials, further implicating their complex involvement in cellular processes.